2011
DOI: 10.1590/s0102-311x2011000600008
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between levels of income inequality and dental caries and periodontal diseases

Abstract: The objective of this study was to evaluate the association between income inequality at a lagged time of 2 and 11 years with two short latency outcomes (untreated dental caries and gingivitis) and two long latency outcomes (edentulism and periodontal attachment loss > 8mm). We used data from the Brazilian oral health survey in 2002-2003. Our analysis included 13,405 subjects aged 35-44 years. Different lagged Gini at municipal level were fitted using logistic and negative binomial multilevel analyses. Cova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 41 publications
2
49
0
7
Order By: Relevance
“…34 In another study on the effect of a public policy that ensured community-based oral health programs, untreated caries prevalence was higher in municipalities where the rate per inhabitant of preventive care was lower. 35 Another possible explanation relates to behavioral factors. Behaviors such as smoking, dietary habits, physical activity and alcohol consumption could account for health-related social inequalities.…”
Section: When Structure and Context Mattermentioning
confidence: 99%
“…34 In another study on the effect of a public policy that ensured community-based oral health programs, untreated caries prevalence was higher in municipalities where the rate per inhabitant of preventive care was lower. 35 Another possible explanation relates to behavioral factors. Behaviors such as smoking, dietary habits, physical activity and alcohol consumption could account for health-related social inequalities.…”
Section: When Structure and Context Mattermentioning
confidence: 99%
“…This finding confirms previous reports on the importance of investigating the impact of contextual factors on oral health outcomes. 8,9,10,28 Moreover, most children who participated in our study had their first dental visit after the age of 4 years. Only 14 children went to the dentist before their first year of life, as recommended by international guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,5,6,7 Nevertheless, recent studies have demonstrated the importance of contextual factors for different oral health outcomes, including the use of dental services. 8,9,10,11,12 In Brazil, the latest official publication showed regional inequality in dental care utilization (SBBRASIL 2010). It is suggested that the economic and social attributes of the community might influence dental care utilization by people who reside in it.…”
Section: Introductionmentioning
confidence: 99%
“…Em um estudo, foi confirmada a associação entre cárie dentária e desigualdade de renda (24) , demonstrando que a abordagem prioritária de grupos com maior risco de adoecer está em consonância com o reordenamento da atenção primária à saúde do SUS e a utilização da estratégia do Programa Saúde da Família. Cabe aos serviços de saúde desenvolver estratégias de prevenção e controle de riscos à saúde através da identificação dos grupos que necessitam de atenção diferenciada do Estado para garantir seus direitos de cidadania.…”
Section: Discussionunclassified